Production of pancreatic progenitor cells from human induced pluripotent stem cells using a three‐dimensional suspension bioreactor system. (20th March 2017) - Mihara, Yuichiro; Matsuura, Katsuhisa; Sakamoto, Yoshihiro; Okano, Teruo; Kokudo, Norihiro; Shimizu, Tatsuya
Abstract: Islet replacement is a promising strategy for the treatment of patients with type 1 diabetes and patients who have undergone total pancreatectomy. Recent progress in cellular reprogramming technology may allow the transplantation of a patient's own pancreatic cells. Although many studies have reported the differentiation of pancreatic progenitor cells from mouse and human pluripotent stem cells (PSCs), obtaining sufficient cell numbers for clinical applications remains problematic. Here, we describe the mass production of human pancreatic progenitor cells from human induced (i)PSCs using a three‐dimensional suspension bioreactor system. Bioreactor culture of cells with stage‐specific provision of growth factors and small compounds for 17 days produced approximately 1.6 × 10 8 cells/100 ml vessel in a single batch. About 95% of cells expressed pancreatic and duodenal homeobox factor 1, and 22% co‐expressed the transcription factor NKX6.1. Furthermore, culture of pancreatic progenitor cells for an additional 2 weeks yielded mature pancreatic cells, including C‐peptide‐, glucagon‐ and trypsin‐expressing cell populations. Moreover, differentiated β‐cells secreted insulin in response to increased glucose in vitro . These findings suggest that a three‐dimensional suspension culture system can generate human pancreatic progenitor cells from human iPSCs. Further optimization of culture conditions should provide sufficient functional islet cells for transplantation therapy. Copyright © 2017 John Wiley & Sons, Ltd.